Visual Communication in Corporate Brands: A Semiological Discourse Analysis of car Brochures - Khan, Mamona; Amjad, Noreena; Rubab, Iram (International Journal of Psychosocial Rehabilitation, 2020)
The process of marketization has greatly been accelerated by the use of visual communication. The companies publish brochures using various semiotic modes to promote their products and cope with the product promotion rivalry. Brochures let your product speak for itself and communicate with the consumers and attract their attention. The present study attempts to explore the semiotic features in car brochures as they play an important part in business communication in convincing people towards a specific communicative goal. It also aims to analyze the brochures ‘images and how these images are used to establish relations with the costumers. The study, as such, is essentially qualitative in nature and placed within interpretive paradigm. Following purposive sampling, two brochures of Toyota (2014) and Honda (2017) have been selected and analyzed using the model of Kress & Leeuwen’s “Semiotic Analysis” (2006). The results of this study indicate that a complex set of relationship is established between the image and their viewers through visuals. The companies use specific visual strategies including contextualization, illumination and representation effectively to enhance the content. Moreover, different color composition and texts are used to achieve their marketing goals; the popularity of the brand and to establish seller-buyer relationship successfully. It was revealed that use of high modulation in the setting create reliability and credibility of the product. Finally, the Findings also revealed how discourses influence society The present study will be helpful in enhancing the comprehension of how different companies use visuals as strategic tool to establish corporate identity in general and the semiotic organization and underlying meaning structure in the brochures of Honda and Corolla car in particular. It will also contribute in providing useful insights to the market researchers